The performance of vocational high school principal’s learning supervision in Indonesia - Lia Yuliana; Johan Setiawan; Muhammad Rijal Fadli (International Journal of Evaluation and Research in Education (IJERE), 2023)
Supervision of learning is one of the most important parts of improving the quality of education. It is necessary to develop an evaluation instrument that can assess the performance of school principals’ learning supervision, to achieve national education goals that accord the needs of the times. So, the purpose of this study is to produce an instrument for assessing the learning supervision performance of the head of vocational high school (VHS) that can be used as a reference for supervisors. The method used is research and development (R&D) with a 4D model defined, designed, developed, and disseminated. The research subjects involved 20 school supervisors, 218 principals, and 314 teachers. Data collection techniques employed interviews, questionnaires, and documentation. Data analysis used the qualitative analysis techniques (interviews) and quantitative analysis (statistics). The results showed that this assessment instrument is an excellent category with an average score of 4.21. This assessment consists of three assessor components: school supervisors, teachers, and school principals. This assessment instrument can be the latest guideline for supervisors who will evaluate the performance of school principals and teachers, so the evaluation carried out is effective, efficient, and optimal in improving the quality of education.